Analisis Penentuan Pusat Ibu Kota Kabupaten Kepulauan Ambon Sebagai Calon Daerah Otonomi Baru Kecamatan Salahutu - Botanri, Adnan Affan Akbar; Ruman, Rifyan; Layn, Usman Gumanti (HORIZON: Indonesian Journal of Multidisciplinary, 2024)
The expansion of Salahutu and Leihitu sub-districts into candidates for the new autonomous region of Ambon Islands Regency has become an interesting issue in recent years in Maluku Province because of various problems that occur such as the difficulty of administrative management such as identity cards, lack of infrastructure and supporting facilities for community activities, control span problems, and various other problems. The feasibility study of Salahutu District to become a new autonomous region has been carried out and in terms of population availability and area has a good level of feasibility. This research is to find out the appropriate location to become the center of the capital of the Ambon Islands Regency based on the availability of regional facilities. The analysis used is the centrality index. This analysis is used by calculating the number of means compared to the population. The results showed that the priority of the central capital of Ambon Islands Regency as a candidate for the new autonomous region of Salahutu District, namely Tulehu Country with a value of 1,168.2 because it has more complete facilities than other villages / countries based on education, health, trade and services, financial institutions and worship. The importance of the results of this research is as a basis if expansion will be carried out and it is necessary to determine the center of the capital, so that the main problems of span of control in Central Maluku can be resolved and provide useful planning for the community